Surface tension driven flow of blood in a rectangular microfluidic channel: Effect of erythrocyte aggregation - Pasias, Dimitris; Passos, Andreas; Constantinides, Georgios; Balabani, Stavroula; Kaliviotis, Efstathios (My University, 2020)
Microfluidic platforms have increasingly been explored for in vitro blood diagnostics and for studying complex microvascular processes. The perfusion of blood in such devices is typically achieved through pressure-driven setups. Surface tension driven blood flow provides an alternative flow delivery option, and various studies in the literature have examined the behavior of blood flow in such fluidic devices. In such flows, the influence of red blood cell (RBC) aggregation, the phenomenon majorly responsible for the non-Newtonian nature of blood, requires particular attention. In the present work, we examine differences in the surface tension driven flow of aggregating and non-aggregating RBC and Newtonian suspensions, in a rectangular microchannel. The velocity fields were obtained using micro-PIV techniques. The analytical solution for blood velocity in the channel is developed utilizing the power law model for blood viscosity. The results showed that RBC aggregation has an impact at the late stages of the flow, observed mainly in the bluntness of the velocity profiles. At the initial stages of the flow, the shearing conditions are found moderately elevated, preventing intense RBC aggregate formation. As the flow decelerates in the channel, RBC aggregation increases, affecting the flow characteristics.
Keywords: Erythrocyte aggregation; Microchannel; Laplace pressure; Flow visualization; Velocimetry; Blood cells; Non Newtonian fluids; Haemodynamics; Rheological properties; Capillary flows